The effect of keeping technology on the microbiological status of raw milk - Peles, Ferenc; Máthéné Szigeti, Zsuzsa; Béri, Béla; Szabó, András (Acta Agraria Debreceniensis, 2008)
The importance of the quality of raw milk increased after Hungary had joined to the EU. On delivery of raw milk, the microbiological quality, especially total plate count of the milk is very important. Twenty-two farms (7 large, 4 medium-sized, and 11 small farms) were included in the study. We considered the different farm size, keeping- and milking circumstances during the selection of farms. The examined large farms use loose housing system (cubicle, deep litter) and milking parlour. Most of them use preand post-milking disinfection. In the medium-sized farms, loose, deep litter and tie-stall housing system, as well as milking parlour, pipeline milking and bucket milking occurred. All of them use preand post-milking disinfection. Small farms use tie-stall housing system, bucket milking and udder preparation by water. Unfortunately, they do not use pre- or post-milking disinfection. In the large and medium-sized farms mainly Holstein Friesian, in the small farms Hungarian Simmental breeds can be found. The aim of our research was to examine the microbiological status of the raw milk produced in dairy farms (total plate count, coliform count, Escherichia coli count, Staphylococcus aureus count, psychrotroph bacteria count, furthermore yeast and mold count); sources of the contamination; connection between the microbiological quality of produced milk and housing-, milking technologies of farms; furthermore the hygienic circumstances of milking and milk handling of the farms, by the examination of coliform bacteria and Escherichia coli contamination. During the examination of the connection between the different farm sizes, various housing- and milking forms and the microbiological characteristics we observed similar tendencies in the case of total plate count, coliform count, yeast and molds count, furthermore psychrotroph bacteria count. The value of these parameters was significantly higher in small farms, and infarms which use tie-stall housing forms, bucket milking, udder preparation with water, and which do not use pre- and post-milking disinfection. The results showed that besides cooling, the milking procedure and the type of udder preparation had the largest effect on the total plate count. Statistical analysis shows that in medium and small farms the combination of pipeline milking – tie stall housing system – disinfectant preparation of the udder; in large farms the combination of milking parlour – loose cubicle housing system – dry preparation of the udder are the most appropriate in the aspect of the total plate count. We experienced that in farms where the hygienic instructions are not followed – and therefore equipment used during the milking and handling of milk is very contaminated – or rather the separation of mastitic cows’ milk is not appropriate, different microorganisms may contaminate the produced milk.